Quality of Life of Emergency Department Nurses in Makassar Hospitals on Work Stressors and Job Satisfaction - Ramli, Rachmat; Ardenny, Ardenny; Prihatini, Surya; Djunaedi, Djunaedi; Rante, Anshar; Mesa, Nofita Dewi Kok (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
Hospitals as organizations can place clients and caregivers under a serious burden of stress, which then affects their physical and emotional health. Working conditions in nursing show that work stress can have a big impact on the quality of life of nurses. The aim of this research was to determine the relationship between work stress, job satisfaction and individual characteristics with the quality of life of nurses in the Emergency Unit at Makassar General Hospital. The research method is descriptive using a cross sectional design with a quantitative approach. The results of the study concluded that there was a relationship between age (p value = 0.04), marital status (p value = 0.02), work stress (p value = 0.004) and job satisfaction (0.04) with the quality of life of nurses. However, there was no relationship between gender (p value = 1.00) and level of education (p value = 0.9) with nurses' quality of life. The most dominant factor related to quality of life is work stress. Work stress will affect the quality of life of nurses who work in the emergency room. Work stress affects the quality of life of emergency room nurses. Job satisfaction is related to the quality of life of emergency department nurses. The nurse's age is related to the quality of life of emergency department nurses. The gender of the nurse is not related to the quality of life of emergency department nurses. Nursing education is related to the quality of life of emergency department nurses. Nurses' marital status is related to the quality of life of emergency department nurses.